Pengintegrasian dan Penguatan Wawasan Kebangsaan pada Masyarakat sebagai Upaya Mencegah Radikalisasi dan Menumbuhkan Cinta Tanah Air di Desa Kemuning Kabupaten Karanganyar - Musyaffa Izzul Haq; Muh Reva Fitra Rahmawan; Alfian Rosyidan Al-haq; Risa Nurul Akbar; Kundharu Saddhono (Jurnal Insan Pengabdian Indonesia, 2024)
Integrating and strengthening national insight in society is an important step to maintain social stability, prevent radicalization, and foster love for the homeland. The phenomenon of radicalization and extremism can threaten the peace and security of a country, so efforts to prevent radicalization need to be realized through a holistic approach, one of which is through strengthening national insight. Strengthening national insight involves a deep understanding of national identity, history, culture and shared values as citizens. Various national problems related to the decline in tolerance for differences and pluralism require understanding and strengthening national values. Pancasila as the basis of the state has a vital role in facing various crises, especially moral crises. Kemuning Village was chosen as the location for the socialization because it is still trying to instill national values and maintain local cultural wisdom. Through the Participatory Action Research (PAR) method, service activities in Kemuning Village are carried out in the planning, implementation and evaluation stages. The aim is to instill national values and overcome societal divisions. Evaluations are carried out to measure the effectiveness of implementing national values in people's daily lives. The results include the socialization of national values and insight, the implementation of these values by society, and the role of community leaders in supporting the implementation of national values. It is hoped that this project can make a positive contribution in strengthening national awareness, increasing national resilience, and overcoming the challenges of the times that continue to develop. assessment timing, more coordinated data management, and the improved capabilities of teachers in overcoming obstacles. The APBAKUS application played a crucial role in enhancing the quality of educational services at the State Special School in Banjarbaru City, enabling teachers to provide better services tailored to the needs of special needs children. Thus, community service reflects the spirit of assisting and improving the quality of education for children who require special attention within the community.